Pengaruh Jenis Bahan Pengkaya Dan Takaran Kompos Biochar terhadap Pertumbuhan Dan Hasil Kacang Hijau (Vigna radiata L. ) di Tanah Entisol Semiarid - Timoteus Abi (Savana Cendana, 2020)
This study aims to determine several types of biochar compost and the appropriate dose on the growth and yield of green beans in dry land. Furthermore, to determine the response of green beans to the application dose of biochar compost. This research was carried out in the experimental field of the Faculty of Agriculture, University of Timor, Sasi Village, Kota Kefamenanu District, TTU Regency from June to November 2019. The design used in this study was a 3x3 strip plot design. 3 times. The first faktor is biochar compost which consists of 3 levels, namely pure biochar, chicken manure biochar compost, and cow manure biochar compost. Meanwhile, in the second faktor, the dose of biochar compost is: 0 tons/ha, 5 tons/ha and 10 tons/ha. The results showed that: there was no interaction between all variables observed in mung bean (Vigna Radiata L.), the level of treatment for the type of enrichment material was not significantly different in all observation parameters, while the level of treatment for biochar compost was 5 t/ha and 10 t/ ha is not significantly different in all observation parameters.